Functional Nanomaterials and Devices for Electronics, Sensors and Energy Harvesting - Nazarov, Alexei; Balestra, Francis; Kilchytska, Valeriya; Flandre, Denis (Engineering Materials,, 2014)
This book contains reviews of recent experimental and theoretical results related to nanomaterials. It focuses on novel functional materials and nanostructures in combination with silicon on insulator (SOI) devices, as well as on the physics of new devices and sensors, nanostructured materials and nanoscaled device characterization. Special attention is paid to fabrication and properties of modern low-power, high-performance, miniaturized, portable sensors in a wide range of applications such as telecommunications, radiation control, biomedical instrumentation and chemical analysis. In this book, new approaches exploiting nanotechnologies (such as UTBB FD SOI, FinFETs, nanowires, graphene or carbon nanotubes on dielectric) to pave a way between "More Moore" and "More than Moore" are considered, in order to create different kinds of sensors and devices which will consume less electrical power, be more portable and totally compatible with modern microelectronics products.